2012
DOI: 10.1111/j.1574-6941.2012.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and dynamics of biostimulated indigenous oil-degrading microbial consortia from the Irish, North and Mediterranean Seas: a mesocosm study

Abstract: Diversity of indigenous microbial consortia and natural occurrence of obligate hydrocarbon‐degrading bacteria (OHCB) are of central importance for efficient bioremediation techniques. To investigate the microbial population dynamics and composition of oil‐degrading consortia, we have established a series of identical oil‐degrading mesocosms at three different locations, Bangor (Menai Straits, Irish Sea), Helgoland (North Sea) and Messina (Messina Straits, Mediterranean Sea). Changes in microbial community comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
3
23
1
Order By: Relevance
“…Most obvious is the separation of the early sampling points (days 0-10) in the upper right section of Fig. 2 from the bulk of the late sampling points (days [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. This trend coincides with the peaks of both emulsification (days 10-12 in both treatments) and protein production (days [12][13][14][15][16][17][18][19][20], which is strongly supported by the ANOSIM results presented in Supplementary Table 1c.…”
Section: Dynamic Changes In Microbial Community Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most obvious is the separation of the early sampling points (days 0-10) in the upper right section of Fig. 2 from the bulk of the late sampling points (days [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. This trend coincides with the peaks of both emulsification (days 10-12 in both treatments) and protein production (days [12][13][14][15][16][17][18][19][20], which is strongly supported by the ANOSIM results presented in Supplementary Table 1c.…”
Section: Dynamic Changes In Microbial Community Compositionmentioning
confidence: 99%
“…Sequencing was performed at Macrogen (Amsterdam, Netherlands) with primers F530 and R1492. The processing and assembly of DNA sequences as well as testing for chimeric sequences was conducted using BioEdit as described before [2,16]. Sequence alignment was performed against a database of validly published reference DNA sequences of typed strains using ClustalW [30].…”
Section: Isolation 16s Rrna Gene Sequencing and Phylogenetic Analysimentioning
confidence: 99%
See 2 more Smart Citations
“…Studies performed after the marine BP Deepwater Horizon oil spill in 2010 in the Gulf of Mexico in the United States showed that the oil leak resulted in the enrichment of bacteria belonging to the Oceanospirillales order and Colwellia and Cycloclasticus genera (5)(6)(7). In addition, members of the Oceanospirillales were detected as the major constituents of the bacterial community in different studies on oil-polluted marine ecosystems (8,9). However, microbial succession in petroleum-contaminated environments depends on the hydrocarbon fractions available to the microbial community, as suggested previously by McKew et al (10).…”
mentioning
confidence: 99%